2012
DOI: 10.1021/la300806m
|View full text |Cite
|
Sign up to set email alerts
|

Independently Controlling Protein Dot Size and Spacing in Particle Lithography

Abstract: Particle lithography is a relatively simple, inexpensive technique used to pattern inorganics, metals, polymers, and biological molecules on the micro- and nanometer scales. Previously, we used particle lithography to create hexagonal patterns of protein dots in a protein resistant background of methoxy-poly(ethylene glycol)-silane (mPEG-sil). In this work, we describe a simple heating procedure to overcome a potential limitation of particle lithography: the simultaneous change in feature size and center-to-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…The shape of the pattern motif is a circle and is determined by a combination of bead-size and the duration of aluminum deposition 9,13 . Alternative techniques for controlling the dot size have also been suggested 14,17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…The shape of the pattern motif is a circle and is determined by a combination of bead-size and the duration of aluminum deposition 9,13 . Alternative techniques for controlling the dot size have also been suggested 14,17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…In colloid lithography, polystyrene spheres in solution are deposited on a surface, and as the solvent evaporates, the spheres form a regular, packed monolayer (Taylor et al, 2012 ) (Figure 6 A). Spheres are then deformed by exposing them to a temperature gradient, which melts the spheres differentially based on the heat applied.…”
Section: Methods To Create Substrate-bound Protein Gradientsmentioning
confidence: 99%
“…(A) By applying a heat gradient under the surface, microspheres melt and interact with the surface to different extents thereby creating a gradient of dots of different size. Adapted with permission from Taylor et al ( 2012 ). Copyright 2012 American Chemical Society.…”
Section: Methods To Create Substrate-bound Protein Gradientsmentioning
confidence: 99%
“…Recently, methods for creating concentration gradients of ions [7], small molecules [8], peptides [9], proteins [10], physiological parameters of the extracellular matrix [11,12] and cells [13] have been developed to construct research environments that mimic those found in vivo. To generate these gradients, diffusion [14], heat [15], gravity [16], electric force [17], light [18] and precise fluid control using microfluidic devices [12,[19][20][21][22] have been used. However, in most of these previous studies, the source of the biological compound was fixed in position and the concentration gradient remained constant over time with a predetermined spatial pattern.…”
Section: Introductionmentioning
confidence: 99%